Seminal papers in orthopaedic oncology. Issue 4 (August 2018) - McCormack, D.J.; Pollock, R.C.; Ashford, R.U.
Abstract: The management of a patient with a tumour of the musculoskeletal system has progressed over recent decades. The development of evidence based medicine is a key factor in driving such change. Although now predominantly treated within specialist centres, all orthopaedic surgeons require an understanding of such malignancies and the management options available to the patients affected. We review the literature in three main areas; soft-tissue sarcoma (STS), primary malignant bone tumours and skeletal metastases. We take a critical look at the papers which have helped shape modern practice, and offer discussion into their relevance. We have given a historical perspective to demonstrate key themes in tumour surgery, and given examples of on-going research to provide an understanding of current developments.